Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1063/1.3506695
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence on crystalline structure and interfacial reactions in HfO2 films on InP (001) grown by atomic layer deposition

Abstract: The crystalline structure and interfacial reactions in HfO2 films grown on InP (001) substrates was investigated as a function of film thickness. High resolution transmission electron microscopy and x-ray diffraction measurements were used to investigate changes in the crystalline structure of the HfO2 films. As the thickness of the HfO2 increased, the crystal structure was transformed from monoclinic to tetragonal, and the interfacial layer between the HfO2 film and the InP substrate disappeared. High resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 8 publications
3
34
0
Order By: Relevance
“…11,13 However, another in situ XPS report of ALD HfO 2 "half cycle" at a substrate temperature of 250 C has shown consistent results with this study, where the In-oxide concentration is seen to decrease and the P-oxide concentration remains constant during the initial ALD stages. 15 This contradiction between ex situ and in situ results from the thin oxide films (less than 2 nm) is possibly due to the interfacial oxide regrowth, and this oxidation is seen to be enhanced by increased substrate temperature upon removal from the ALD reactor.…”
Section: Resultssupporting
confidence: 83%
“…11,13 However, another in situ XPS report of ALD HfO 2 "half cycle" at a substrate temperature of 250 C has shown consistent results with this study, where the In-oxide concentration is seen to decrease and the P-oxide concentration remains constant during the initial ALD stages. 15 This contradiction between ex situ and in situ results from the thin oxide films (less than 2 nm) is possibly due to the interfacial oxide regrowth, and this oxidation is seen to be enhanced by increased substrate temperature upon removal from the ALD reactor.…”
Section: Resultssupporting
confidence: 83%
“…Hence, this may reduce the In outdiffusion upon annealing. While both In and PO 2 diffusion through HfO 2 were observed in previous reports using TOF-SIMS, [9][10][11] the detection limit of TOF-SIMS (7 Â 10 7 /cm 2 ) is significantly lower than LEIS (3.3 Â 10 11 /cm 2 ) and ARXPS (majority of distribution), 18,30 so it is assumed that the concentration of diffused P is below the limit of detection for LEIS and XPS but sufficient to be detected by TOF-SIMS.…”
mentioning
confidence: 54%
“…8 An et al and Kang et al have reported diffusion of In atoms and P-oxides through a thick (>6 nm) HfO 2 layer on InP by Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS). [9][10][11] However, detailed analysis of this substrate elemental diffusion through other high-k dielectrics as well as interfacial chemistry upon annealing has not been reported.…”
mentioning
confidence: 98%
“…The strong tendency of In-diffusion is reflected from recent studies of In diffusion through high-k dielectrics in (HfO 2 and Al 2 O 3 )/InP stacks. 22,23 For the acid etched and the S-passivated samples, prior to ALD, relatively low concentrations of Ga 2 O and GaPO 4 ÁxH 2 O states are detected compared with the native oxide sample. After annealing in the ALD reactor, an increase in the concentration of Ga-oxides is observed.…”
mentioning
confidence: 98%